Uneven terrain affects metabolic cost and gait in simulated complex lunar surfaces - Kim, Kyoung Jae; Baughman, Alexander; Estep, Patrick; Rivas, Eric; Young, Millennia; Marshall-Goebel, Karina; Abercromby, Andrew; Somers, Jeffrey (Physiological measurement, 2023)
Objective . Upcoming missions of the National Aeronautics and Space Administration (NASA) to the Moon will include extensive human exploration of the lunar surface. Walking will be essential for many exploration tasks, and metabolic cost during ambulation on simulated complex lunar surfaces requires further characterization. In this study, ten healthy subjects (6 male and 4 female) participated in three simulated lunar terrain walking conditions at the NASA Johnson Space Center’s planetary ‘Rock Yard’: (1) flat terrain, (2) flat terrain with obstacles, and (3) mixed terrain. Approach. Energy expenditure and gait were quantified with a wearable metabolic energy expenditure monitoring system and body-worn inertial measurement units (IMUs), respectively. Main results. It was found that participants walking on the mixed terrain, representing the highest workload condition, required significantly higher metabolic costs than in other terrain conditions ( p < 0.001). Additionally, our novel IMU-based gait variables discriminated different terrains and identified changes in gait in simulated lunar terrain environments. Significance. Our results showed that the various surface irregularities and inconsistencies could cause additional physical effort while walking on the complex terrain. These findings provide insight into the effects of terrain on metabolic energy expenditure during simulated lunar extravehicular activities.